Ultra-Low-Power and Ultra-Low-Cost Short-Range Wireless Receivers in Nanoscale CMOS - Lin, Zhicheng; Mak (Elvis), Pui-In.; Martins, Rui Paulo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides readers with a description of state-of-the-art techniques to be used for ultra-low-power (ULP) and ultra-low-cost (ULC), short-range wireless receivers. Readers will learn what is required to deploy these receivers in short-range wireless sensor networks, which are proliferating widely to serve the internet of things (IoT) for "smart cities." The authors address key challenges involved with the technology and the typical tradeoffs between ULP and ULC. Three design examples with advanced circuit techniques are described in order to address these trade-offs, which specially focus on cost minimization. These three techniques enable respectively, cascading of radio frequency (RF) and baseband (BB) circuits under an ultra-low-voltage (ULV) supply, cascoding of RF and BB circuits in current domain for current reuse, and a novel function-reuse receiver architecture, suitable for ULV and multi-band ULP applications such as the sub-GHz ZigBee. ·         Summarizes the state-of-the-art in ultra-low-power (ULP) wireless receivers; ·         Includes novel, ultra-low-power and ultra-low-cost (ULC), analog and RF circuit techniques--from concepts to practice; ·         Describes and demonstrates the first RF-to-baseband current-reuse 2.4GHz receiver and the first gain-boosted function-reuse sub-GHz receiver, with ULP and ULC in 65nm CMOS.  .
Introduction -- Design and Implementation of Ultra-Low-Power ZigBee/WPAN Receiver -- A 2.4-GHz ZigBee Receiver Exploiting an RF-to-BB-Current-Reuse Blixer + Hybrid Filter Topology in 65-nm CMOS -- Analysis and Modeling of a Gain-Boosted N-Path Switched-Capacitor Bandpass Filter -- A 0.5-V 1.15-mW 0.2-mm2 Multi-Band ZigBee Receiver Using Function Reuse and Gain-Boosted N-Path Techniques for IoT Applications -- Conclusion.
Keywords: Electronic circuits; Telecommunication; Electronics; Electronic Circuits and Systems; Communications Engineering, Networks; Electronics and Microelectronics, Instrumentation